Allochthonous and autochthonous carbon flows in food webs of tropical forest streams. (28th March 2017) - Neres‐Lima, Vinicius; Machado‐Silva, Fausto; Baptista, Darcilio F.; Oliveira, Renata B. S.; Andrade, Pedro M.; Oliveira, Andrea F.; Sasada‐Sato, Cristiano Y.; Silva‐Junior, Eduardo F.; Feijó‐Lima, Rafael; Angelini, Ronaldo; Camargo, Plínio B.; Moulton, Timothy P.
Abstract: The River Continuum Concept (RCC) assumes that autochthonous primary production in forest streams is limited by light and is insufficient to sustain secondary production by consumers; they must therefore depend on allochthonous carbon from the surrounding forest. Recent studies have, however, questioned the importance of allochthonous carbon in stream food webs. There is a growing body of evidence using stable‐isotope techniques that demonstrate the importance of algae (autochthonous production) in the food webs of tropical streams. The actual contributions of autochthonous and allochthonous resources are rarely evaluated accurately because few studies consider the diet and the trophic efficiencies of the components of the food web or measure primary and secondary production to estimate the energy flow. We estimated the annual net primary productivity of periphytic microalgae (NPP) and the secondary production of macroinvertebrates (SP) from empirical models and we used stable isotopes of carbon and nitrogen to quantify the flow of material in food webs of five forest streams in the Guapi‐Macacu catchment, Rio de Janeiro, Brazil. NPP ranged from 46 g to 173 g dry mass (DM) m −2, whereas SP ranged from 0.90 g DM m −2 to 2.58 g DM m −2 . The contribution of allochthonous carbon to the SP was more important than autochthonous sources and varied from 56% to 74% of all basal energy flow assimilated by primary consumers. The annual ingestion rate of basal sources varied from 8.08 g DM m −2 to 26.57 g DM m −2, with the allochthonous material contributing 76% and 87% of this. The annual ingestion rate of autochthonous material varied from 1.2% to 5.5% of the NPP. The present work suggests that the principal energy source for macroinvertebrates in streams of the Guapi‐Macacu catchment came from the riparian forest, as predicted by the RCC. However, this dependence appeared not to be driven by an absolute lack of autochthonous NPP, which seemed more than sufficient to sustain the entirety of macroinvertebrate SP.